The Evaluation of International Relationship Role in Promotion of Health System Research - M Ghanei; HH Kohanzad; P Owlia (Tehran University of Medical Sciences, 2013)
Background: Regarding the need for scientific development and achievement our national goals, it is clear that international cooperation has the main role in this way. Here is a report on what we have done during past almost 10 years (2001-2011) in the field of international medical research activities in Deputy Ministry for Research & Technology, Ministry of Health, Iran. Our effort was focused to identify and contact with the prominent scientific centers among the world where could make a connection between our researchers in medical science universities with those centers.